Measuring Profit Efficiency of Colombian Banks: A Composite Nonstandard Profit Function Approach (2018)
We analyze the profit efficiency of the Colombian banking industry during theperiod 2001 - 2013. Unlike previous studies, we estimate revenue and cost efficiencyseparately and then compute profit efficiency as a composite measure of both costand revenue efficiency. This approach overcomes the mis-specification problems ofthe traditional nonstandard profit function approach used in most of the literatureregarding profit efficiency. We find that profit efficiency improved during the periodunder analysis mainly because gains in revenue efficiency. In addition, and in contrastwith previous studies but in line with economic intuition, we find that while revenue andcost efficiency tend to be negatively correlated, each correlates positively with profitefficiency. Thus, improving either revenue efficiency or cost efficiency has a positiveimpact on profit efficiency.